ANALISIS FAKTOR KENDALA FUNDRAISING PADA LEMBAGA ZAKAT DI INDONESIA - Aksen Tias, Muhamad; Majaya, Dhafin; Dzikry Rizkyawan, Mohammad; Ardiansyah, Alfian; Tiarahman, Robi (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2024)
According to the year-end report of 2021, the national zakat collection amounted to 14 trillion Indonesian Rupiah. However, in 2022, BAZNAS (National Amil Zakat Agency) was only able to collect zakat funds amounting to Rp 546 billion, still falling below the potential figure. The method used was qualitative descriptive with a conceptual analysis model. This research relied on secondary data sources with literature review techniques and content analysis methods. The findings of this study highlight several issues in the collection and distribution of zakat funds in Indonesia. The primary factors limiting zakat collection include low literacy and inadequate human resources quality, encompassing insufficient public knowledge, individual distribution tendencies, and a lack of awareness regarding zakat obligations.